On All-Unity in the Process of Cognition (On Some Aspects of V. Solovyov’s Gnoseology) - Šliogeris, Arvydas (Problemos, 1973)
The article is devoted to the gnoseological views of V. Solovyov, a Rusian idealist philosopher. The author of the article shows that in spite of V. Solovyov’s attempts to overcome “one-sidedness” of the gnoseology of European rationalistic idealism, the theory of cognition as suggested by V. Solovyov is found to be none other but an endeavour to “supplement” the gnoseology of German idealists with mystical elements. Thus the Hegelian pan-logicism was replaced by a peculiar pan-mysticism since the Hegelian Reason as the basis of the world unity was replaced by the mystical All-Unity on the basis of which V. Solovyov believed to overcome the dualism of the subject and object. The author finds the cognition mechanism suggested by V. Solovyov to be a mystified Kantianism supplemented with some elements of Plato’s theory of ideas. In this way the theory of gnoseology by V. Solovyov is found to be a retrogression as compared with the gnoseological conceptions or the German idealists since V. Solovyov restored to life the tradition of the medieval scholasticism and theology.